IMPROVING STUDENT’S WRITING SKILL OF PROCEDURE TEXT BY USING PICTURE SERIES OF EIGHT GRADE YEAR STUDENT SMP IT AN-NAAS BINJAI - Ade Wahyuni Azhar (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The objective of the study is to find out the improvement Students’ Writing Skill Of Procedure Text By Using Picture Series Of Eigh Grade Year Student SMP IT An-Naas Binjai In Academic Year 2017/2018. The subjects of this study are students who sit in class VIIISMP IT An-Naas BinjaiAcademic Year 2017/2018 there are 32 Students consisting of 13 Men and 19 Women. And the object in this study is all student in eight grade SMP IT An-Naas Binjai. The improvement of this classroom action research can be known from the learning process and the result of the writing of the Student Text Procedure after being given action by using picture series. Improvement of the process can be seen from the motivation of student learning to be better with the student’s enthusiasm in writing procedure text with the existence of picture picture will facilitate students in making dialog in procedure text, students’ imagination become more developed, and student literature appreciation woke up well. In cycle I, 22 students are failed and 10 students are good. In cycle II, 5 students are failed, 23 students are good and 4 students are Very good.From the results of this study it can be concluded that the use of picture picture series can improve the ability of writing procedure text students.